2018
DOI: 10.1021/acsami.8b00853
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistive Graphene Sensors for Ammonia Detection

Abstract: The primary objective of this work is to demonstrate a novel sensor system as a convenient vehicle for scaled-up repeatability and the kinetic analysis of a pixelated testbed. This work presents a sensor system capable of measuring hundreds of functionalized graphene sensors in a rapid and convenient fashion. The sensor system makes use of a novel array architecture requiring only one sensor per pixel and no selector transistor. The sensor system is employed specifically for the evaluation of Co(tpfpp)ClO func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 57 publications
0
90
0
1
Order By: Relevance
“…Figure 6b displays the self-discharge curve of the stretchable MSCs without the microsensor, and the inset is a digital photograph of stretchable MSCs integrated with a microsensor. [49] To highlight the diverse applications of our fabricated stretchable MSCs, NiO/Co 3 O 4 /LIG patterns (a simple 16 cm 2 square geometry) were embedded in the WPU to prepare a TENG. From the curve, the WPU microsensor shows sensitivity and rapid response characteristics that vary with different pressures obtained by pressing with different fingers.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6b displays the self-discharge curve of the stretchable MSCs without the microsensor, and the inset is a digital photograph of stretchable MSCs integrated with a microsensor. [49] To highlight the diverse applications of our fabricated stretchable MSCs, NiO/Co 3 O 4 /LIG patterns (a simple 16 cm 2 square geometry) were embedded in the WPU to prepare a TENG. From the curve, the WPU microsensor shows sensitivity and rapid response characteristics that vary with different pressures obtained by pressing with different fingers.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…From these two applications, we observe that MSC arrays can provide a stable working voltage for the sensor, which suggests the stability and feasibility of our stretchable MSCs as a driving source for wearable electronics. [49] To highlight the diverse applications of our fabricated stretchable MSCs, NiO/Co 3 O 4 /LIG patterns (a simple 16 cm 2 square geometry) were embedded in the WPU to prepare a TENG. By assembling stretchable MSC arrays to a TENG in combination with an all-wave rectifier, a self-charging power unit was achieved.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…These problems can be solved by an appropriate decoration of CNT and graphene surfaces with metal nanoparticles. Functionalization of these carbon nanostructures is utilized to attach metal nanoparticles like Pt, Ag, Au, Al, Cu, Sn, Pd which enable selective sensing of gases like H 2 , NH 3 , NO 2 , CH 4 , H 2 S, and CO [321][322][323][324] and their oxides [325][326][327][328][329]. More information about CNTs, graphene gas sensors may be found in [318,320,330].…”
Section: Hybrid Structuresmentioning
confidence: 99%
“…Environmental (relative) humidity is an important factor that affects the stability of the device. [6,49] Therefore, the effect of humidity on sensor performance to trimethylamine (TMA) at a concentration of 2110 ppm was examined at different relative humidities (RHs 10, 50, and 90 %R H, 25 8C) with both NA-3Tand NA-3T-NA-baseds ensors. Figure S9 in the SupportingI nformationd epicts the results from three replicated tests.…”
Section: Molecular Conformation In Single Crystalsmentioning
confidence: 99%
“…[1][2][3][4] The World Health Organization (WHO) has confirmed that high levels of BAs in spoiled foods could lead to diseases and abnormal activities in the central nervous system. [5,6] About 600 millionp eople get sick every single year, and more than 400 000 peopled ie from unhygienicf oods. [7] Therefore, various techniques, such as quartz crystal microbalance; [8,9] localized surfacep lasmon resonance; [10] radiofrequency identification; [11,12] Raman spectroscopy; [13] and electrochemical, [14,15] fluorescent, [16][17][18][19][20][21][22] and colorimetric sensors, [23,24] have been developed and used for detecting BAs to monitorf ood spoilage.…”
Section: Introductionmentioning
confidence: 99%